Bifunctional Azido(thio)ureas from an O-Protected 2-Amino-2-deoxy-d-glucopyranose: Synthesis and Structural Analyses - Concepción Sosa-Gil; Esther Matamoros; Pedro Cintas; Juan C. Palacios (Molecules)
This publication reports a facile and convenient preparation of tri-O-acetyl-glucopyranoses, derived from the corresponding 2-deoxyaminosugar, where the vicinal anomeric and C2 positions are decorated by azido and (thio)ureido groups, respectively. This double functionalization leads to an inherently chiral core incorporating the versatile azido and (thio)ureido linkages prone to further manipulation. The latter also provides a structural element for hydrogen-bonded donor-acceptor (HB-DA) sites, which are of immense value in organocatalytic pursuits. A computation-aided conformational analysis unveils the landscape of available conformers and their relative stability. N-aryl (thio)ureas bearing substituents at ortho positions exist as mixtures of M- and P-atropisomeric conformers.